PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TIPE PEER INSTRUCTION BERBASIS VIDEO INTERAKTIF TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X PADA MATA PELAJARAN AKIDAH AKHLAK - Kartika Hidayati; Sholikah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The development of technology in education has opened up new opportunities for the application of innovative learning models, including in the teaching of Aqidah Akhlak. However, in reality, students' critical thinking skills are still relatively low because the learning methods used are still conventional. Based on this, this study aims to describe the implementation of the Flipped classroom learning model of the Peer instruction type based on interactive video, identify the critical thinking skills of grade 10 students, and test the effect of the model on improving students' critical thinking skills in the subject of Aqidah Akhlak at MA Hasyimiyah Sukolilo Bancar. This study uses a quantitative approach with a quasi-experimental design (Non-Equivalent Control Group Design). The research sample consisted of 37 students divided into an experimental group (19 students) and a control group (18 students). Data collection techniques include tests (pre-test and post-test), observation, and documentation. Data analysis was carried out using SPSS 27 through normality tests, homogeneity tests, and independent sample t-tests. The results of the study indicate that the implementation of the Flipped classroom model of the Peer instruction type based on interactive video is categorized as very good (91.6%). Before the implementation (pre-test), the average critical thinking ability score of the experimental group was 59.22 and the control group was 57.00. After the implementation (post-test), the average score of the experimental group jumped significantly to 85.94, while the control group was only 71.50. The t-test results showed a significance value (2-tailed) <0.001 <0.05, which proved a significant difference in influence. Thus, it can be concluded that the Flipped classroom learning model of the Peer instruction type based on interactive video is effective in improving students' critical thinking abilities in the subject of Akidah Akhlak..